Syntheses and characterizations of multifunctional polyphenols derived from dihydroxyphenylene-based Schiff bases - Kaya, Î.; Keskin, Ş (Polimery, 2013)
Schiff base compounds were synthesized by condensation reaction of 1,4-diaminobenzene, naphthalene-1,5-diamine and 2,6-dichlorobenzene-1,4-diamine compounds with 2,4-dihydroxybenzaldehyde. The obtained Schiff bases were converted to their polyphenol derivatives by oxidative polycondensation. Sodium hypochlorite and air were used as the oxidants. Experimental parameters such as temperature, reaction time and oxidant concentration were varied to determine the optimum oxidative polycondensation conditions. The structures of all compounds were confirmed by FT-IR, UV-Vis and 1H- and 13C NMR analyses. In addition, thermal properties of the Schiff bases and the corresponding polymers were determined by TG-DTA, DSC and DMA techniques. Photoluminescence properties of the synthesized compounds were determined in DMF solutions. Electrochemical characterizations were made by cyclic voltammetry measurements. Solid state conductivities of the polymers were determined by four point probe technique using an electrometer. The number average and weight average molecular weights and polydispersity index values of the synthesized compounds were determined by the size exclusion chromatography.